Effect of laser shock processing on residual stress and fatigue behavior of 6061-T651 aluminum alloy - 任旭东 张永康 周建忠 冯爱新 (Transactions of Nonferrous Metals Society of China, 2006)
Laser shock processing is a very new technique and an emerging modem process that generates compressive stresses much deeper into the surfaces of metals or alloys. A brief parametric study of the effect of laser parameters on fatigue behavior and residual stress state generated in 6061-T651 alloy specimens was summarized. Residual stress of 6061-T651 alloy was analyzed both before and after laser processing with multishocks. The material remains in compressive residual stress of approximate 1 mm in depth which is approximately 10 times deeper than that can be achieved with the conventional technique, and the maximal compressive residual stress at the surface of the sample is about -350MPa. Near the surface, yield strength and hardness are found to be increased by the laser shock. The ratio of fatigue crack initiation life for the laser-shocked to unshocked specimens is found to be 4.9 for specimens. The results clearly show that LSP is an effective surface treatment technique for improving the fatigue performance of aluminum alloys.